Preparation, characterization and evaluation of fenofibrate: benzoic acid cocrystals with enhanced pharmaceutical properties - Braham Dutt; Manjusha Choudhary; Vikas Budhwar (SpringerOpen, 2021)
Abstract Background Cocrystallization process involved the understanding of interaction at molecular level between two molecules in context to their crystal packing and designing of new solids having improved physicochemical as well as pharmaceutical properties. In the present research, an attempt to increase the aqueous solubility and dissolution rate of a poorly aqueous soluble drug fenofibrate (FB) by formulation and evaluation of its cocrystals with benzoic acid (BZ) as a coformer was carried out. Results The drug and coformer were cocrystallized by using the solvent drop grinding method. For prediction of cocrystals formation, CSD (Cambridge Structure Database) software was utilized. Fourier transformation infrared spectroscopy (FTIR), X-ray diffraction (XRD) and differential scanning calorimetry (DSC) techniques were used for analysis of cocrystals. Albino rats were procured from institution as per IAEC guidelines for in vivo anti-hyperlipidaemic studies. The in vitro dissolution profile of cocrystals, pure drug, their physical mixture and marketed formulation was found to be 89%, 39%, 47% and 61%, respectively. Conclusions An enhanced anti-hyperlipidaemic activity of cocrystals was found compared to pure drug. The FB: BZ cocrystals also compared to the pure drug showed better dissolution profile and improved in vivo anti-hyperlipidaemic activity in rats. The study proved that cocrystals can promise to improve in vitro dissolution rate of poorly aqueous soluble drugs, which in turn can lead to better in vivo activities.